Cartel enforcement in the European Union: Determinants of the duration of investigations - Kai Hüschelrath; Ulrich Laitenberger; Florian Smuda (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2012)
We provide an empirical assessment of EC cartel enforcement decisions between 2000 and 2011. Following an initial characterisation of our dataset, we especially investigate the determinants of the duration of cartel investigations. We are able to identify several key drivers of investigation length such as the Commission's speed of cartel detection, the type of cartel agreement, the affected industry or the existence of a chief witness.
urn:nbn:de:bsz:180-madoc-326231
Keywords: 330; Competition Policy; Empirical Analysis; Cartels; European Union; Fines; Leniency; Duration of Investigation; Kartellrecht; Dauer; Rechtsdurchsetzung; Wettbewerbspolitik; EU-Staaten